Pengaruh Digitalisasi Sistem Informasi Manajemen Rumah Sakit Terhadap Efektivitas Administrasi Pasien - Rohmah, Faizatur; Widodo, Ayudisty Ristika Kusumawardhani; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Innovative: Journal Of Social Science Research, 2025)
Digitalization in the healthcare sector, particularly through the implementation of Hospital Management Information System (SIMRS), has become a primary focus in enhancing the effectiveness of patient administration. The aim of this study is to analyze the impact of SIMRS digitalization on the effectiveness of patient administration. The method employed is a literature review, which examines various relevant journals and previous studies on this topic. The analysis results indicate that SIMRS digitalization improves patient administration, as evidenced by service speed, data accuracy, ease of access to information, and patient satisfaction. Although there are challenges in implementation, such as infrastructure constraints and human resource readiness, the benefits derived from this digital system far outweigh the drawbacks. The conclusion of this study demonstrates that digitalization through SIMRS has a significant positive impact on the effectiveness of patient administration.